Synergetic radiosensitization effects of bismuth oxide nanoparticles, cisplatin and baicalein-rich fraction from oroxylum indicum combinations for clinical radiotherapy - Sisin, Noor Nabilah Talik (2021)
Multimodal strategies of cancer treatment aim to eradicate complex malignant disease with enhanced therapeutic outcome with combined synergetic effects in contrast to individual techniques that might exhibits some limitations. Chemotherapeutic drug such as cisplatin have been applied to increase radiation doses at target tissues in radiotherapy. However, commercial chemo-drugs toxicities had compelled the researchers to evaluate alternatives for non-toxic agents and radiosensitizers, potentially from natural derivatives or metal-based nanoparticles (NPs). Integration of novel nanomaterials and natural product as radiosensitizer to increase the anti-tumors efficacy are also promising to enhance the treatment performance. This study aimed to investigate the synergetic radiosensitization effects of bismuth oxide NPs (BiONPs), cisplatin (Cis) and a baicalein-rich fraction (BRF) from Oroxylum indicum (OI) leaves extract under clinical radiotherapy of High Dose Rate (HDR) brachytherapy, photon, and electron beams. The cytotoxicity, cellular uptake, and reactive oxygen species (ROS) generation induced by BiONPs were initially investigated on MCF-7 and MDA-MB-231 breast cancer as well as NIH/3T3 normal fibroblast cell lines in elucidating the BiONPs feasibility for radiotherapy application. The safe concentration of Cis and BRF were also determined prior irradiation. Quantification of radiosensitization effects and ROS generation were conducted with individual BiONPs, Cis, and BRF, as well as BiONPs-Cis (BC), BiONPs-BRF (BB) and BiONPs-Cis-BRF (BCB) combinations for High Dose Rate (HDR) brachytherapy, photon, and electron beams. Raman Spectroscopy and apoptosis analysis were conducted to elucidate the subcellular biochemical changes and cells death mechanism. The cytotoxicity results provide that the BiONPs induced minimal cell deaths constituting less than 20% on average while ROS production by BiONPs was negligible. The increment of NPs cellular uptake indicated that BiONPs were internalized and bound to the cellular surfaces. Consequently, 0.5 mM of 60 nm BiONPs was found to be an optimum concentration and size for radiotherapy application. The lowest values of the 25% of inhibition concentration by individual Cis and BRF obtained were 1.30 μM and 0.76 μg/ml, respectively, and utilized for the subsequent experiments. Investigation of the radiosensitization effects among the treatment components indicated the highest SER value by BC combination in MCF-7 cells, followed by BCB and BB treatments. The effects were more prominent for Ir- 192 of γ-radiation compared to photon and electron beams. Meanwhile, the combination treatments present the higher ROS levels for photon beam than brachytherapy and electron beam. The highest ROS enhancement was attributed to the presence of BC combination in MDA-MB-231 cells. Interestingly, the BCB combination also showed a high SER but collaterally affected the normal cells. The BC combination of MCF-7 cells showed potential as an effective radiosensitizer for brachytherapy with the early apoptosis predominantly occurred within 40 hours after irradiation. Finally, the finding from Raman spectroscopy demonstrated that the BiONPs-Cis and brachytherapy combination would affect the glycolysis process, the amino acid structure arrangement and the DNA/RNA stability that would suggest the enhancement of radiation effects on cancer cells. In conclusion, this study suggests the potential of BiONPs, Cis and BRF as radiosensitizer that could improve the efficiency of radiotherapy to eradicate the cancer cells. The combination of these potent radiosensitizers could produce synergetic effects that will elevate the therapeutic impact of clinical radiotherapy.